1984
DOI: 10.1128/aac.25.3.387
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antifungal activities of amphotericin B and liposome-encapsulated amphotericin B

Abstract: The in vitro activities of lipsome-encapsulated amphotericin B and free amphotericin B against Candida albicans 336 were comparable. Amphotericin B concentrations 12-fold and greater than 50-fold higher were required to kill the same organism when cholesterol and ergosterol were incorporated into the liposomes. The addition of cholesterol to liposomes caused a significant increase in the minimal fungicidal concentration of amphotericin B in 7 of 19 other yeast strains tested, whereas ergosterol caused an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
4
2

Year Published

1986
1986
2006
2006

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(31 citation statements)
references
References 6 publications
0
25
4
2
Order By: Relevance
“…Alguns investigadores relataram eficiência terapêu-tica equivalente entre AmBisome e AB-DOC (Hopfer, Mehta, Lopez-Berestein, 1987), enquanto outros encontraram significativa redução na atividade antifúngica para a formulação lipídica (Hopfer et al, 1984;. Pahls e Schaffner (1994) também compararam AmBisome com AB-DOC quanto à atividade antifúngica in vitro e em modelos de candidíase sistêmica e localizada em camundongos imunocomprometidos.…”
Section: Estudos Em Animaisunclassified
See 1 more Smart Citation
“…Alguns investigadores relataram eficiência terapêu-tica equivalente entre AmBisome e AB-DOC (Hopfer, Mehta, Lopez-Berestein, 1987), enquanto outros encontraram significativa redução na atividade antifúngica para a formulação lipídica (Hopfer et al, 1984;. Pahls e Schaffner (1994) também compararam AmBisome com AB-DOC quanto à atividade antifúngica in vitro e em modelos de candidíase sistêmica e localizada em camundongos imunocomprometidos.…”
Section: Estudos Em Animaisunclassified
“…Segundo os autores, isto ocorreu devido ao fato de que 50% de AB não se apresentava encapsulada nesta formulação. Hopfer et al (1984) relataram resultados semelhantes com lipossomas preparados com DMPC:DMPG. Desta forma, os autores propuseram que a necessidade de maior tempo de incubação influenciaria a atividade antifúngica devido à liberação da AB encapsulada.…”
Section: Estudos Que Avaliaram Formulações Tipo Ab-lipossômicaunclassified
“…Amphotericin-B acts as an ionophore, com¬ bining with sterols (predominantly ergosterol) in the fungal cytoplasmic membrane to form porous channels (Kinsky, 1962;Feingold, 1965). The ability of amphotericin-B to bind to cholesterol and ergosterol has been well documented (De Kruijff et al, 1974;Hopfer et al, 1984). Cholesterol is a major lipid component of cell membranes, interacting with phospholipids within the membrane, modulating membrane fluidity (Whetton et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Liposome encapsulation of AmpB has been demonstrated to enhance the therapeutic index of the drug (7,(9)(10)(11)(12) partly by decreasing toxicity to human erythrocytes (RBC) while maintaining its in vivo antifungal efficacy (10). Studies from our laboratory have shown that AmpB and liposomal AmpB (L-AmpB) have comparable antifungal activity in vitro against several strains of Candida albicans (7). Antifungal activity has also been improved by using drug combinations (1,6,11,13).…”
mentioning
confidence: 95%
“…However, despite its efficacy, the drug has severe side effects that are related to its interaction with the plasma membranes of mammalian cells (1,4,5,8). Liposome encapsulation of AmpB has been demonstrated to enhance the therapeutic index of the drug (7,(9)(10)(11)(12) partly by decreasing toxicity to human erythrocytes (RBC) while maintaining its in vivo antifungal efficacy (10). Studies from our laboratory have shown that AmpB and liposomal AmpB (L-AmpB) have comparable antifungal activity in vitro against several strains of Candida albicans (7).…”
mentioning
confidence: 99%